Representational changes of latent strategies in rat medial prefrontal cortex precede changes in behaviour - Nathaniel James Powell (Nature Portfolio, 2016)
The medial prefrontal cortex (mPFC) is involved in changing behavioural strategies. Recording neural ensembles in rats, Powell and Redish find that the requirement for those changes is represented in mPFC before they manifest behaviourally, both in tasks that externally force a change and in tasks with self-determined change.